APLIKASI STEGANOGRAFI UNTUK MENYISIPKAN PESAN DALAM MEDIA IMAGE - Nunung Nurmaesah; Tutik Lestari; Arni Retno Mariana (LPPM STMIK Pringsewu, 2017)
In the course of employment, the employee is not uncommon to find the problems in the software and hardware used. However, handling the problem by system developers must be done in the initiation and control of the project to be or underway, because recording is still a simple process that affects the performance of the company. This can have a negative impact, ie, there is a risk of problems noted repeatedly, the problem is not an accurate calculation and a long wait to get a report. For the software development process using UML models (The Unified Modeling Language). Done starting from the identification and analysis of problems, requirements analysis, system design, system implementation and testing. PHP and Database Management System (DBMS) MySQL will be used for the preparation of the information system. With the implementation of this application is expected to facilitate the processing of data and generate reports quickly and accurately which can be used for corporate decision-making.